2018
DOI: 10.1007/s11896-018-9277-x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Traumatic Stress: Prevalence and Symptomology Amongst Detective Officers Investigating Child Protection Cases

Abstract: It has been increasingly recognised that individuals exposed to the trauma of others within their professional roles can be affected by secondary traumatic stress (STS). Despite this recognition, there is a dearth of literature examining the prevalence of secondary traumatic stress amongst police officers in the UK. This study aims to meet this gap. Sixty-three Detective Officers from Family Protection Units (FPU(s)), primarily engaged in child protection/abuse investigations, self-reported their experiences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 39 publications
5
29
2
2
Order By: Relevance
“…The type of intervention and the exposure to persons who have experienced one (or more) traumatic events could vary and thus influence the STS symptoms. As suggested by MacEachern et al (2019) , disturbing material (such as child pornography or intimate partner violence; Zara and Gino, 2018 ) greatly increases the symptoms of STS. Further research must investigate the exposure to and the type of traumatic events in which POs have to intervene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The type of intervention and the exposure to persons who have experienced one (or more) traumatic events could vary and thus influence the STS symptoms. As suggested by MacEachern et al (2019) , disturbing material (such as child pornography or intimate partner violence; Zara and Gino, 2018 ) greatly increases the symptoms of STS. Further research must investigate the exposure to and the type of traumatic events in which POs have to intervene.…”
Section: Discussionmentioning
confidence: 99%
“…As described by MacEachern et al (2019), other definitions have also been used to describe the consequences that result from working with traumatic events. These definitions include vicarious trauma and compassion fatigue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no other existing research to make direct comparisons for this specific group. Nonetheless, several previous studies conducted in different developed countries such as the United States and the United Kingdom used the STSS as an instrument (Bourke & Craun, 2012, 2014; Bride, 2007; Hurrell et al, 2018; MacEachern et al, 2019; Perez et al, 2010; Perron & Hiltz, 2006). The present study found higher levels of STS symptomology among PDOs compared with previous studies conducted in the United Kingdom and the United States.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by MacEachern et al (2011), who assert that there is a high possibility of STS among police officers working with the victims of sexual crime. In addition, a number of studies conducted on police officers have indicated that PDOs report more severe indicators of psychological distress, namely STS, than their counterparts who do not work with victims of sexual crime (Bourke & Craun, 2014; MacEachern et al, 2019; Perez et al, 2010). These PDOs similarly display signs of STS/vicarious trauma (VT), including hyper-vigilance, recurrent and intrusive distress, difficulty concentrating, relationship problems, lack of communication, denial, repression, avoidance, isolation, disassociation, change in worldviews, and loss of a sense of meaning (Bourke & Craun, 2012; MacEachern et al, 2011; Tovar, 2011).…”
Section: Sts and Police Officersmentioning
confidence: 99%